Eurosensors 2018 2018
DOI: 10.3390/proceedings2131512
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Monolithic Integration of Converter Circuitry and Piezoelectric MEMS Energy Harvesters

Abstract: One of the main difficulties for a global implantation of the Internet of Things (IoT) is the energy dependence of the nodes, limited by the battery's lifetime. Energy harvesting seems to be a promising solution to provide energy autonomy to IoT nodes. Power management circuits are needed to collect and store the charges scavenged form the ambient sources. In addition, this circuit needs to adapt the output voltage to power the wireless sensor node. Because of the typical heterogeneity of the system, the cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Jordan et al [20] found that when the duty cycle is extremely large, once a 100% duty cycle occurs in a certain cycle, when the next cycle comes, because the switch tube continues to conduct, the sampling current always exists, and the superimposed level drops. If the ramp current is too small compared to the sampling current, the superimposed level bath will quickly reach the error voltage VC within a very short time at the beginning of the next cycle [21], and the switch will be turned off, making the cycle duty cycle smaller. Due to the long conduction time of the freewheel, the inductor current will drop sharply [22], which will lead to continuous conduction in subsequent cycles to maintain the output voltage stability.…”
Section: Related Workmentioning
confidence: 99%
“…Jordan et al [20] found that when the duty cycle is extremely large, once a 100% duty cycle occurs in a certain cycle, when the next cycle comes, because the switch tube continues to conduct, the sampling current always exists, and the superimposed level drops. If the ramp current is too small compared to the sampling current, the superimposed level bath will quickly reach the error voltage VC within a very short time at the beginning of the next cycle [21], and the switch will be turned off, making the cycle duty cycle smaller. Due to the long conduction time of the freewheel, the inductor current will drop sharply [22], which will lead to continuous conduction in subsequent cycles to maintain the output voltage stability.…”
Section: Related Workmentioning
confidence: 99%
“…In this work, we propose the use of a single chip composed by the energy harvester, the power management circuit, and the storage capacitors. With this monolithic integrated circuit based on a CMOS-compatible technology [33], the cost of the energy harvesting system can be reduced. In addition, taking advantage of the silicon area on top of the cantilever and the rest of the chip to add the integrated circuits and capacitors (Figure 10a), the area of the entire system can be reduced.…”
Section: Proposed Monolithic System and Fabrication Processmentioning
confidence: 99%
“…In addition, device encapsulation and packaging usually represents a large part of the manufacturing costs of MEMS devices and integrated circuits [30,31,32]. For these reasons, our goal is to monolithically combine MEMS and CMOS technologies to obtain a fully integrated system comprising of a piezoelectric generator and its associated converter circuit [33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%